KETIKA ATURAN BERTEMU TRADISI: KOEKSISTENSI REGULASI DAN BUDAYA LOKAL DALAM TATA KELOLA DESA - Andriyawan E. Karim; Niswatin Niswatin; Tri Handayani Amaliah (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This article examines how formal regulations and local culture can coexist in village governance in Indonesia. Using a qualitative research methodology based on an extensive literature review of leading indexed academic journals, particularly Sinta and Scopus, this study carefully analyzes the complex interplay between strict legalistic rules and deeply rooted socio-cultural practices, including but not limited to mutual cooperation (gotong royong), community deliberations (musyawarah), and the crucial role played by traditional leaders within these communities. The study's findings illuminate the idea that the overall effectiveness and efficiency of village governance is influenced not solely by the level of compliance with formal regulations, but rather by the village's capacity to effectively internalize and integrate local cultural values ​​into the process of policy formulation and implementation. This complex coexistence of formal regulations and local cultural practices ultimately culminates in the development of a governance model that is not only more adaptive and participatory but also significantly more sustainable in the long term.